Brief Report: Cobicistat Compared With Ritonavir as a Pharmacoenhancer for Atazanavir in Combination With Emtricitabine/Tenofovir Disoproxil Fumarate. (1st July 2015) - Gallant, Joel E.; Koenig, Ellen; Andrade-Villanueva, Jaime F.; Chetchotisakd, Ploenchan; DeJesus, Edwin; Antunes, Francisco; Arastéh, Keikawus; Rizzardini, Giuliano; Fehr, Jan; Liu, Hui C.; Abram, Michael E.; Cao, Huyen; et al.
Abstract : Background: Cobicistat (COBI) is a pharmacoenhancer with no antiretroviral activity. Methods: International, randomized double-blind active-controlled trial to evaluate the efficacy and safety of COBI vs ritonavir (RTV) as a pharmacoenhancer of atazanavir in combination with emtricitabine/tenofovir disoproxil fumarate in HIV treatment-naive patients followed through week 144. Results: At Week 144, virologic suppression was achieved in 72% (COBI) and 74% (RTV) of patients. Adverse events leading to study drug discontinuation occurred in 11% of patients in each group. Median changes in serum creatinine (mg/dL) were +0.13 (COBI) and +0.07 (RTV) and were unchanged from week 48. Conclusions: Once-daily COBI is a safe and effective pharmacoenhancer of the protease inhibitor atazanavir.